The causes and consequences of microbial community structure - Ashley Shade (Frontiers Research Topics, 2015)
The causes and consequences of differences in microbial community structure, defined here as the relative proportions of rare and abundant organisms within a community, are poorly understood. Articles in "The Causes and Consequences of Microbial Community Structure", use empirical or modeling approaches as well as literature reviews to enrich our mechanistic understanding of the controls over the relationship between community structure and ecosystem processes. Specifically, authors address the role of trait distributions and tradeoffs, species-species interactions, evolutionary dynamics, community assembly processes and physical controls in affecting 'who's there' and 'what they are doing'.